Fabrication and characterization of scaffolds containing different amounts of allantoin for skin tissue engineering - Yeganeh Dorri Nokoorani (Nature Portfolio, 2021)
Abstract Using the skin tissue engineering approach is a way to help the body to recover its lost skin in cases that the spontaneous healing process is either impossible or inadequate, such as severe wounds or burns. In the present study, chitosan/gelatin-based scaffolds containing 0.25, 0.5, 0.75, and 1% allantoin were created to improve the wounds’ healing process. EDC and NHS were used to cross-link the samples, which were further freeze-dried. Different in-vitro methods were utilized to characterize the specimens, including SEM imaging, PBS absorption and degradation tests, mechanical experiments, allantoin release profile assessment, antibacterial assay, and cell viability and adhesion tests. The results indicated that the scaffolds’ average pore sizes were approximately in the range of 390–440 µm, and their PBS uptake amounts were about 1000% to 1250% after being soaked in PBS for 24 h. Around 70% of the specimens were degraded in 6 days, but they were not fully degraded after 21 days. Besides, the samples showed antibacterial activity against S. aureus and E. coli bacteria. In general, the MTT cell viability test indicated that the cells’ density increased slightly or remained the same during the experiment. SEM images of cells seeded on the scaffolds indicated appropriate properties of the scaffolds for cell adhesion.